The application of planned experiment for determination of welded girder diflection - Vlastimir, Palić (Journal of Production Engineering, 1984)
In this paper two factorial planned experiment for determining the welded girder difiection was applied. The possibility for elimination of residual girder directed deformation during welding process by changing of the heat energy, in order to avoid afterwords straihtening, was investigated.